Women's preferences for men's facial masculinity are strongest under favorable ecological conditions - Urszula M. Marcinkowska; Markus J. Rantala; Anthony J. Lee; Mikhail V. Kozlov; Toivo Aavik; Huajian Cai; Jorge Contreras-Garduño; Oona A. David; Gwenaël Kaminski; Norman P. Li; Ike E. Onyishi; Keshav Prasai; et al. (NATURE PUBLISHING GROUP, 2025)
The strength of sexual selection on secondary sexual traits varies depending on prevailing economic and ecological conditions. In humans, cross-cultural evidence suggests women's preferences for men's testosterone dependent masculine facial traits are stronger under conditions where health is compromised, male mortality rates are higher and economic development is higher. Here we use a sample of 4483 exclusively heterosexual women from 34 countries and employ mixed effects modelling to test how social, ecological and economic variables predict women's facial masculinity preferences. We report women's preferences for more masculine looking men are stronger in countries with higher sociosexuality and where national health indices and human development indices are higher, while no associations were found between preferences and indices of intra-sexual competition. Our results show that women's preferences for masculine faces are stronger under conditions where offspring survival is higher and economic conditions are more favorable.